Evaluation of the Problems of General Dental Practitioners in the Usage of Composite Materials in Posterior Teeth in the City of Isfahan-Iran in 2010 - Parvin Mirzakoucheki Boroujeni; Mehrdad Barekatain; Samaneh Alaei; Ahmad Shahnazari (Mashhad University of Medical Sciences, 2013)
Introduction: Posterior composite restorations are the one of the most usual dental treatments among patients. The goal of this study was determining dentists' problems during and after treatment of posterior - composite restorations in the city of Isfahan.Materials & Methods: In this descriptive-analytical study, we used a questionnaire including questions about the problems of posterior composite treatments during and after operation among dentists in Isfahan in 2009-2010. The data were analysed by chi-Square test.Results: The most frequent problem during composite restoration was achieving good proximal contact (30.8%) and after it, sensitivity of teeth while chewing which would not be repaired by correct occlusion (34.8%). Most of the dentists pushed the matrix strip toward the adjacent teeth while polymerization, applied the composite in different layer, did the company instructions for bonding layer and used wet polishing during restoration. Most of the dentists (55.8%) used two step total etch dentinal bonding and selected the composite because of its ability in making isolation and good restoration (42.5%).Conclusion: Providing correct education for the dentists and increasing their knowledge about these restorations result in reduction of associated problems during and after the operation.